Exploring The Multitarget Pharmacological Mechanism of Diabex for T2dm by Combining Network Pharmacology and Molecular Docking Techniques - Megha M (International Journal of Bioinformatics and Computational Biology, 2023)
Objective: Hyperglycemia brought on by an absolute or relative absence of insulin synthesis or action characterises a set of illnesses known as diabetes mellitus. Chronic hyperglycemia in diabetes mellitus has been linked to organ damage, heart, and blood vessels. The persistent metabolic condition Diabetes is a severe global issue with negative social, health, and economic effects. It is a type of metabolism disorder that interferes with food digestion in the body. The pancreas produces less or no insulin because of diabetes, and the cells either do not react to the created insulin or do not respond at all. Methods: In this study, the binding affinity and the derivatives of the targeted proteins were evaluated IRS1, APOE, AND PPARG. PyRx tool was used to carry out the molecular docking. The study was carried out computationally, utilizing protein and phytocompound information and structure from DrugBank, GeneCards, and PubChem. The protein structure was examined using the BIOVIA discovery studio software. ADMET screening was used to examine the ligands' pharmacological characteristics. Results: The phytocompounds stigmasterol, kaempferol, cholesterol, beta-sitosterol, luteolin, and quercetin had the highest binding affinity against the targeted protein after docking. Conclusion: According to the findings, these active ligands have anti-diabetic efficacy. Exploring Diabex's Multitarget Pharmacological Mechanism for Type 2 Diabetes Using Network Pharmacology and Molecular Docking Techniques.
Keywords: Diabetes mellitus; binding affinity; molecular docking; network pharmacology; pharmacological properties